Exploration of TPACK in Upper Level School in Indonesia EFL Teacher’s View - Rufina Wilda Toding; Abd Halim; Amirullah Abduh (International Journal of Language, Education, and Literature, 2025)
The advancement of learning in the 21st century is closely tied to various information technology tools. Consequently, educators must enhance their ICT skills to improve both teaching effectiveness and student academic performance. This study has two main objectives: (1) to examine how TPACK is implemented in the teaching and learning process, and (2) to identify the challenges English teachers face when applying the TPACK framework in their instruction. A qualitative research approach was used, incorporating observations and interviews as data collection methods. The study focused on an English teacher and students from Class XI MIPA 2 at Senior High School 13 Makassar. The TPACK knowledge of the English teacher is reflected in how effectively technology aligns with pedagogical strategies and subject knowledge. By integrating technology, the teacher can apply diverse instructional strategies across different learning environments, following the Merdeka Curriculum. This approach allows students to learn at their own pace and according to their individual preferences. To facilitate teaching and assessment, the English teacher used Quizizz and Google Classroom for managing assignments and providing timely feedback. However, inconsistent network connectivity significantly impacted student engagement and learning equity. Since TPACK-based instruction relies heavily on online resources, limited internet access became a major obstacle. Additionally, web-based platforms and multimedia materials require a stable internet connection for effective classroom integration. Interruptions in connectivity disrupted activities such as live quizzes, direct assessments, and online group projects, which are essential for helping students master complex English concepts. To address these challenges, institutions must invest in technological infrastructure and provide teachers with the necessary support and training to effectively adapt to various situations and ensure the successful implementation of TPACK in English education. Keywords: TPACK, High School, English language